Hubungan Posisi Kerja dengan Kejadian Musculoskeletal Disorders pada Kelompok Petani Di Desa Waiheru Kecamatan Baguala, Kota Ambon - Idham Soamole; Windarti Rumaolat; Anggraini Hamdun (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2025)
Musculoskeletal disorders are health problems involving joints, muscles, tendons, skeleton, cartilage, ligaments, and nerves. The causes of MSDs are gender, age, length of service, awkward working posture, repetitive movements to bad exercise habits. The level of MSDs from the lightest to the most severe will interfere with concentration at work, cause fatigue,, and ultimately reduce productivity. The purpose of the study was to analysis the relationship of work position with the incidence of musculoskeletal disorders in farmers groups in Waiheru village, Baguala District, Ambon City. This type of research uses analytic observational design with a cross-sectional approach. The sample in this study amounted to 59 and sampling using cluster random sampling technique. The instruments used were the Ovako work analysis system (OWAS) observation sheet and the Nordic Body Map (NBM) questionnaire. Data analysis using Spearman rank test. The results of the study based on statistical Spearman rank test obtained p-value value = 0.005, where the value of α < 0.05. So that Ha is accepted, it means that there is a significant relationship between work positions and the incidence of musculoskeletal disorders in farmer groups in Waiheru Village, Baguala District, Ambon City.Keywords: Complaints, Farmers, Musculoskeletal disorders, Nordic Body Map, Work position